2021
DOI: 10.3390/agronomy11071408
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Agar Bioassay Sensitivity Test in Alopecurus myosuroides for the Pre-Emergence Herbicides Cinmethylin and Flufenacet

Abstract: Rapid and reliable tests for pre-emergence herbicide susceptibility in weeds are important to test a wider range of accessions on their baseline sensitivity, as well as to provide information on putative resistance. This study focused on the development of an agar quick test to determine sensitivity differences in Alopecurus myosuroides Huds. to pre-emergence herbicides containing flufenacet and cinmethylin. The new agar quick test and a standardized whole plant pot bioassay were conducted twice in 2019. For b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Indeed, it was shown that multipleherbicide resistant biotypes of Lolium rigidum or Alopecurus myosuroides biotypes with resistance to flufenacet can be effectively controlled by cinmethylin. [38][39][40] Identification of alternative FAT inhibitors for use in wheat or other crop systems will strengthen and diversify the tools for weed management. The herein identified new FAT inhibitors lay the groundwork for the development of new herbicides with this newly identified SoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was shown that multipleherbicide resistant biotypes of Lolium rigidum or Alopecurus myosuroides biotypes with resistance to flufenacet can be effectively controlled by cinmethylin. [38][39][40] Identification of alternative FAT inhibitors for use in wheat or other crop systems will strengthen and diversify the tools for weed management. The herein identified new FAT inhibitors lay the groundwork for the development of new herbicides with this newly identified SoA.…”
Section: Discussionmentioning
confidence: 99%
“…For the control of increasing numbers of herbicide resistant weeds with target site or non‐target site resistances, there is a dire need for new active ingredients and ideally SoAs. Indeed, it was shown that multiple‐herbicide resistant biotypes of Lolium rigidum or Alopecurus myosuroides biotypes with resistance to flufenacet can be effectively controlled by cinmethylin 38–40 . Identification of alternative FAT inhibitors for use in wheat or other crop systems will strengthen and diversify the tools for weed management.…”
Section: Discussionmentioning
confidence: 99%
“…Among the monocot plants, the use of Agrostis stolonifera L. and Alopecurus myosuroides Huds. seeds [ 35 , 36 ], as well as several species of aquatic macrophytes of the genus Lemna (e.g., L. paucicostata Hegelm., L. minor L., L. gibba L.) [ 37 , 38 ], was adapted for bioassays. In the screening programs conducted by Chinese researchers, Brassica campestris L., Cucumis sativus L., Amaranthus retroflexus L., Digitaria sanguinalis (L.) Scop., Echinochloa crus-galli L.) P. Beauv.…”
Section: Current Trends In Herbicide Developmentmentioning
confidence: 99%
“…99 In Table 4, several recent onfarm, portable, and rapid diagnostic tests for herbicide resistance reported after 2013 are presented in detail to assist the screening of IPS for putative herbicide resistance. Some tests require that the environmental parameters remain stable to provide valid results, 100 while others require cutting-edge sensors and technologies to deliver more robust results. 101 Indicative new technologies, tests, methods, techniques and applications for early weed detection and rapid herbicide resistance screening are presented in Tables 4 and 5.…”
Section: Early Weed Detection and Herbicide Resistance Screening Tool...mentioning
confidence: 99%